PEMBENARAN: SUKACITA DAN HARAPAN DALAM PENDERITAAN - Julia Theis (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
The human desire to eliminate suffering often conflicts with the Apostle Paul’s radical declaration that believers can rejoice in their sufferings. This paradox, how suffering and joy can co-exist is resolved through the doctrine of justification. This paper provides an exegetical study of Romans 5:1-5 to explore the practical application of justification by faith in the contemporary Christian life. By analyzing the historical, literary context, and exegesis of the text, this paper demonstrates that the biblical understanding of justification encompasses both a new status person before God and the new life that this status demands. The exegesis identifies four primary fruits of justification: peace with God, hope in His glory, joy in suffering, and the indwelling of the Holy Spirit. The text also reveals that God uses suffering purposefully to produce perseverance and proven character. This refined character, in turn, strengthens a believer's hope. Ultimately, the study concludes that this hope is not illusory; it is sustained and assured by the Holy Spirit, who pours God's love into the believer's heart and provides comfort so they can rejoice in suffering.